Adjusting Social Mobility of High-quality Science and Technology Human Resources in the Context of International Integration with Financial Policy: A Case Study of Vietnam Academy of Science and Technology - Truong, Dao Thanh; Thi Hoai Thu, Chu (VNU Journal of Science: Policy and Management Studies; Vol 34 No 4DO - 10.25073/2588-1116/vnupam.4161, 2018)
Abstract: In the context of international economic integration, especially the integration of science and technology, along with the development of information technology, social mobility of S&T human resources, especially high-quality human resources, is happening in a vibrant, diverse and complex way. This study examines the mobiliy status at Vietnam Academy of Science and Technology (VAST) as well as VAST’s efforts in setting out policies to ensure the management and development of S&T human resources in both quantity and quality, adjust the human resources mobility, and effectively exploit the existing human resources. The study focuses on the using of financial policies to adjust social mobility, especially social mobility of high-quality human resources, to orient the social mobility of S&T human resources towards certain directions, e.g. mobility from basic research to applied research, as well as to diversify activities to fully exploit the capacity of VAST’s S&T human resources. Keywords: Financial policy, social mobilization, science and technology human resources. References [1] Thủ tướng Chính phủ (2011), Quyết định số 2133/QĐ-TTg ngày 01/12/2011 về “Phê duyệt quy hoạch tổng thể phát triển Viện KH&CN Việt Nam (sau là Viện Hàn lâm KH&CN Việt Nam) đến năm 2020 và định hướng đến năm 2030” [2] Đào Thanh Trường, Nguyễn Thị Ngọc Anh (2018), Chảy chất xám tại chỗ trong bối cảnh cuộc cách mạng công nghiệp 4,0: Một số vấn đề đặt ra, Tạp chí Khoa học ĐHQGHN: Nghiên cứu Chính sách và Quản lý, Tập 34, Số 3 (2018), tr. 1-7 [3] Viện Hàn lâm Khoa học và Công nghệ Việt Nam, Báo cáo hoạt động năm 2012- 2017 của Viện Hàn lâm KH&CN Việt Nam: Lưu hành nội bộ.